A quantum framework for economic science: New directions - Sudip Patra (Kiel Institute for the World Economy (IfW), 2019)
The current paper explores the cutting-edge applications of quantum field theory and quantum information theory modelling in different areas of economic science, namely, in the behavioural modelling of agents under market uncertainty, and mathematical modelling of asset or option prices and firm theory. The paper then provides a brief discussion into a possible extension of the extant literature of quantum-like modelling based on scattering theory and statistical field theory. A statistical theory of firm based on Feynman path integral technique is also proposed very recently. The collage of new initiatives as described in the current paper will hopefully ignite still newer ideas.
Keywords: C00; C02; C18; D40; D80; G12; 330; quantum like modelling; contextuality; QFT (quantum field theory); self-adjoint operators; uncertainty; epistemic; ontic